The effectiveness of technology based (interactive) distance learning methods in a large South African financial services organisation - M. Van Der Spuy; A. Wöcke (South African Journal of Business Management, 2003)
The trend towards technology-based learning (or `e-learning') is increasing, driven largely by anecdotal evidence of advantages. This article compares the effectiveness of the technology supported learner driven distance learning methods to the `traditional' classroom based teaching model and the simulation model. The results of the training methods on a sample of cashiers in a major South African bank are compared and the study finds that there were significant differences between the outcomes of three methods of training that had an impact on performance and knowledge retention with classroom based learning having the greatest impact.
Keywords: 650